Pure tripartite entanglement types based on spectra of reduced density matrices - Molladavoudi, Saeid; Zainuddin, Hishamuddin; Chan, Kar Tim (IOP Publishing, 2013)
Given a specific ordered spectra of (shifted) one-qubit reduced density matrices, we discuss that the pure tripartite entanglement for a system consisting of three qubits is determined by only two local unitary invariant polynomials.